Synergistic Solubilization of Phenanthrene by Mixed Micelles Composed of Biosurfactants and a Conventional Non-Ionic Surfactant - Liu, Jianfei; Wang, Yuru; Li, Huifang (Molecules (Basel, Switzerland), 2020)
This study investigated the solubilization capabilities of rhamnolipids biosurfactant and synthetic surfactant mixtures for the application of a mixed surfactant in surfactant-enhanced remediation. The mass ratios between Triton X-100 and rhamnolipids were set at 1:0, 9:1, 3:1, 1:1, 1:3, and 0:1. The ideal critical micelle concentration values of the Triton X-100/rhamnolipids mixture system were higher than that of the theoretical predicted value suggesting the existence of interactions between the two surfactants. Solubilization capabilities were quantified in term of weight solubilization ratio and micellar-water partition coefficient. The highest value of the weight solubilization ratio was detected in the treatment where only Triton X-100 was used. This ratio decreased with the increase in the mass of rhamnolipids in the mixed surfactant systems. The parameters of the interaction between surfactants and the micellar mole fraction in the mixed system have been determined. The factors that influence phenanthrene solubilization, such as pH, ionic strength, and acetic acid concentration have been discussed in the paper. The aqueous solubility of phenanthrene increased linearly with the total surfactant concentration in all treatments. The mixed rhamnolipids and synthetic surfactants showed synergistic behavior and enhanced the solubilization capabilities of the mixture, which would extend the rhamnolipids application.